Calciphylaxis in Hemodialysis - Sgarabotto, Luca; Anastasio, Paola Baldini; Marchionna, Nicola; Zanella, Monica (Journal of Clinical Nephrology, 2023)
Calciphylaxis (CP) or uremic calcific arterial disease (CUA) is a rare, potentially fatal calcific vasculopathy characterized by calcific and thrombotic occlusion of the vessels of the subcutaneous and dermis leading to extremely painful necrotic lesions. It mainly affects patients with end-stage kidney disease (ESKD) and under long time dialysis. The only therapeutic option is represented by intravenous sodium thiosulfate. Currently, clear guidelines are lacking. We have had a good therapeutic response with doses of sodium thiosulfate in association with multidisciplinary management of the patient (vulnologist, dermatologist, nephrologist, dietitian, and cardiologist). There is limited literature on the use of DOAC therapy as a successful alternative to warfarin in patients on dialysis with calciphylaxis. The left atrial appendage closure could represent an important alternative to dicumarolics in patients with atrial fibrillation with calciphylaxis. A new perspective for the treatment of this disease is SNF472 a selective inhibitor of vascular calcification.